2022
DOI: 10.3390/cimb44050128
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals LncRNAs Associated with Flowering of Angelica sinensis during Vernalization

Abstract: Angelica sinensis is a “low-temperature and long-day” perennial plant that produces bioactive compounds such as phthalides, organic acids, and polysaccharides for various types of clinical agents, including those with cardio-cerebrovascular, hepatoprotective, and immunomodulatory effects. To date, the regulatory mechanism of flowering under the photoperiod has been revealed, while the regulatory network of flowering genes during vernalization, especially in the role of lncRNAs, has yet to be identified. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…In this study, a total of 474 lncRNAs were systematically identified in L. gibba during SA-induced flowering. The lncRNA number was approximately 1.5-fold greater than that identified in L. sativa [48] but was less than that reported in A. sinensis, P. sibirica, and chickpea [17,18,20]. To some extent, these findings demonstrate impact of the species, sequenced depth, and used criteria on the identification of lncRNAs.…”
Section: Expression Verification Of Lncrnasmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, a total of 474 lncRNAs were systematically identified in L. gibba during SA-induced flowering. The lncRNA number was approximately 1.5-fold greater than that identified in L. sativa [48] but was less than that reported in A. sinensis, P. sibirica, and chickpea [17,18,20]. To some extent, these findings demonstrate impact of the species, sequenced depth, and used criteria on the identification of lncRNAs.…”
Section: Expression Verification Of Lncrnasmentioning
confidence: 56%
“…The lncRNAs also showed co-expression with genes relevant to photosynthesis, tetrapyrrole synthesis, jasmonate metabolism, signaling, and transport (Figure 2B), indicating similar roles of lncRNAs in L. gibba during SA-induced flowering. LncRNAs have been evidenced to play comparable roles in the flowering of other species: in A. sinensis, Liu et al [18] found the co-expression of lncRNAs with genes related to carbohydrate metabolism, biosignaling, energy, and transport during vernalization; in P. sibirica, Xu et al [20] revealed that lncRNAs participated in secondary metabolism, hormone signaling, and starch and sucrose metabolism during flowering; in L. sativa and chickpea, lncRNAs were reported to participate in flowering based on their co-expression with protein-coding genes related to photoperiodism, transport, and hormone signaling [17,48]. Most importantly, fifteen lncRNAs were co-expressed with flowering-related genes (including LHY, CCA1a, PI, and SVP) (Figure 4), providing us with excellent hints to further characterize the function of lncRNAs by examining their interactions [4,10].…”
Section: Functional Analysis Of Lncrnas During Sa-induced Floweringmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, autumn bolting (AB) will also happen in the cultivation process in September. Transcriptomics and metabolomics have been employed to investigate the regulatory mechanisms underlying bolting, as well as the reduction in the accumulation of bioactive metabolites and the identification of genes involved in the biosynthesis of ferulic acid, flavonoids, and lignin in A. sinensis, which are associated with the shikimic acid and phenylpropanoid pathways [18][19][20][21]. The AB root is often mistaken for the AS root due to its similar morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%